Framework for estimation of nacelle drag on isolated aero-engines with separate jets - Ramirez-Rubio, Santiago; MacManus, David G. (Sage, 2020)
Typically, the evaluation of nacelle drag in preliminary design is required to find an overall optimum engine cycle and flight trajectory. This work focuses on the drag characteristics of aero-engine nacelles with separate jet exhausts. The main body of analysis comes from 3D numerical simulations. A new near-field method to compute the post-exit force of a nacelle is presented and evaluated. The effects of the engine size, Mach number, mass-flow capture ratio and angle of attack are assessed. The results obtained from the numerical assessments were used to evaluate conventional reduced order models for the estimation of nacelle drag. Within this context, the effect of the engine size is typically estimated by the scaling ratio between the maximum areas and Reynolds numbers. The effect of the angle of attack on nacelle drag is mostly a function of the nacelle geometry and angle of attack. In general, typical low order models based on skin friction and form factor can underestimate the friction drag by up to 15% at cruise operating point. Similarly, reduced order models based solely on Reynolds number and Mach number can underestimate the overall nacelle drag by up to 74% for free stream Mach number larger than the drag rise Mach number.
Keywords: propulsion integration; computational fluid dynamics; nacelle drag; Aero-engine aerodynamics